JURIDICAL REVIEW OF THE RESPONSIBILITY OF CHILDREN AS PERPETRATORS OF THE CRIME OF ABUSE (CASE STUDY: RULING NUMBER 7/PID/SUS.ANAK/2019/PN.JAP): TINJAUAN YURIDIS TERHADAP PERTANGGUNGJAWABAN ANAK SEBAGAI PELAKU TINDAK PIDANA PENGANIAYAAN (STUDI KASUS: PUTUSAN NOMOR 7/PID/ SUS.ANAK/2019/PN.JAP) - Septiman Mendrofa, Rizky (LPPM UPMI, 2023)
This study aims to determine the form of responsibility for children as perpetrators of criminal acts, the legal basis for judges' considerations, and the factors causing the occurrence of criminal acts of abuse in decision Number 7 / Pid / Sus.Anak / 2019 / PN. Jap. The method used is normative research. ABH's actions are in accordance with Article 351 Paragraph (1) of the Criminal Code Jo. RI Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Child offenders are sentenced to imprisonment for 4 (four) months and placed in the State Detention Center. Such detention is contrary to the Juvenile Criminal Justice System which prioritizes restorative justice and diversion for the child of the offender of a criminal act, preferably the child should be placed in a place of guidance. The judge's consideration in deciding the criminal case of persecution is based on the prosecution's indictment, witness statements, defendant's testimony, instructions and evidence relevant to the crime being examined. Factors causing the occurrence of criminal acts of persecution are internal and external factors. Based on his considerations, the Judge ruled that the child's actions had fulfilled the elements of the criminal act of molestation.